Coated steel sheet and its manufacturing method
Patent Information
- Application Number
- JP2023552586
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-06-07
- Filing Date
- 2023-05-15
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2043-05-15
AI Technical Summary
【0033】 本発明によれば、鋼板と金型との間の摩擦係数を顕著に低下させることができる。その結果、本発明によれば、プレス成形時に割れが生じやすい部位においても割れを生じさせることなく成形を行うことができる。また、本発明によれば、面圧の高い部位における型カジリを抑制することができる。したがって、本発明の被覆鋼板は極めて良好なプレス成形性を有しており、複雑な形状への成形にも好適に用いることができる。
Smart Images

Figure 0007632672000008 
Figure 0007632672000009 
Figure 0007632672000010
Abstract
Description
[Technical field]
[0001] The present invention relates to a coated steel sheet, in particular to a coated steel sheet having excellent press formability, and to a method for producing said coated steel sheet. [Background technology]
[0002] Steel sheets such as cold-rolled steel sheets and hot-rolled steel sheets are widely used in various fields, and for example, in applications such as automobile bodies, the steel sheets are generally used after press forming. Therefore, the steel sheets are required to have excellent press formability.
[0003] In particular, in recent years, there has been a trend toward press molding into more complex shapes in order to improve the design of products. In addition, there has been a trend toward integrating parts to simplify the manufacturing process, and in that sense, there has also been a trend toward press molding into more complex shapes.
[0004] However, when a steel sheet is press-formed into a complex shape, the steel sheet may break due to insufficient strength to withstand the forming process, or die galling may occur during continuous press forming. As a result, this has a serious adverse effect on the productivity of products such as automobiles. Therefore, there is a demand for further improvement in press formability.
[0005] As a method for improving press moldability, for example, a method of performing a surface treatment on a mold used for press molding can be mentioned. Although this method is widely used, there is a problem that once the surface treatment is performed, the mold cannot be adjusted thereafter. In addition, there is also a problem of high cost.
[0006] One method for improving press moldability without surface treatment of the die is to use a highly viscous lubricant, but this method results in press molded parts with the highly viscous lubricant adhering to them, which can lead to poor degreasing after press molding, and poor degreasing can lead to poor paintability.
[0007] Therefore, instead of using surface treatments of dies or high-viscosity lubricants, there is a demand for improving the press formability of the steel sheet itself.
[0008] As a technique for improving the press formability of a steel sheet itself, a method of forming a lubricating film on the surface of the steel sheet by performing a surface treatment has been proposed.
[0009] For example, Patent Document 1 proposes a coated steel sheet in which an acrylic resin film is formed on the surface of a zinc-based plated steel sheet.
[0010] Patent Document 2 proposes that in a coated metal sheet in which a resin film is formed on the surface of a metal sheet, a solid lubricant is protruded by 0.01 to 1.5 μm from the surface of the resin film.
[0011] Patent Document 3 proposes coating the surface of a metal product with a film of polyurethane resin containing a lubricant to a thickness of 0.5 to 5 μm.
[0012] Patent Document 4 proposes a coated steel sheet having an alkali-soluble organic coating in which a lubricant is added to an epoxy resin. [Prior art documents] [Patent documents]
[0013] [Patent Document 1] Japanese Patent Application Publication No. 09-170059 [Patent Document 2] Japanese Patent Application Publication No. 10-052881 [Patent Document 3] JP 2000-309747 A [Patent Document 4] JP 2000-167981 A Summary of the Invention [Problem to be solved by the invention]
[0014] However, in the techniques proposed in Patent Documents 1 to 4, although a certain degree of improvement in lubricity was observed due to the effect of the lubricant contained in the coating, the formability in complex press molding was not necessarily sufficient. Specifically, there were problems such as cracks occurring in areas where cracking is likely to occur during press molding, and die galling occurring in areas where the surface pressure is high.
[0015] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a coated steel sheet having excellent press formability. [Means for solving the problem]
[0016] The present inventors have focused on coated steel sheets having a coating film containing an organic resin and a wax, and as a result of extensive research to solve the above problems, have come to the following findings.
[0017] (1) When a steel sheet coated with a film containing organic resin and wax is press-formed, the film is scraped off by the die as the film surface slides against the die surface, and a lubricating film, which is a mixture of the organic resin and wax in the film, covers the sliding surfaces between the die surface and the steel sheet. Therefore, in order to improve press formability, it is necessary to improve the sliding properties of the lubricating film that covers the sliding surfaces between the die surface and the steel sheet, that is, to reduce the coefficient of friction.
[0018] (2) By using a specific organic resin and wax and controlling the area ratio of wax-deficient portions in the coating and the average area of the wax-deficient portions, the coefficient of friction can be significantly reduced.
[0019] The present invention has been made based on the above findings, and the gist of the present invention is as follows.
[0020] 1. A coated steel sheet comprising a base steel sheet and a coating containing an organic resin and wax provided on at least one surface of the base steel sheet, the organic resin is at least one selected from the group consisting of a styrene-based resin, an epoxy-based resin, a phenol-based resin, and a polyester-based resin; The wax is a polyolefin wax having a melting point of 100° C. or more and 145° C. or less and an average particle size of 3.0 μm or less, the coating has a wax-deficient portion, which is defined as a region in which the ratio of the mass of the wax to the mass of the organic resin is 1 / 10 or less, and the area ratio of the wax-deficient portion to the entire coating is 20.0% or less; The average area of the wax deficient portion is 50.0 μm 2 is as follows: The coating weight per side is 0.3 g / m 2 That's it, coated steel sheet.
[0021] 2. The ratio of the organic resin in the coating is 30% by mass or more and 95% by mass or less, 2. The coated steel sheet according to claim 1, wherein the proportion of the wax in the coating is 5% by mass or more and 50% by mass or less.
[0022] 3. The coated steel sheet according to 1 or 2 above, wherein the arithmetic mean roughness Ra of the surface of the substrate steel sheet is 0.4 μm or more and 2.5 μm or less.
[0023] 4. The coating weight per side is 2.5 g / m 2 4. The coated steel sheet according to any one of the above 1 to 3, which is:
[0024] 5. The coated steel sheet according to any one of the above 1 to 4, wherein the organic resin is an alkali-soluble resin.
[0025] 6. The coated steel sheet according to any one of the above 1 to 5, wherein the coating further contains a rust inhibitor.
[0026] 7. The coated steel sheet according to claim 6, wherein the rust inhibitor is at least one selected from the group consisting of aluminum salts of phosphoric acids, zinc salts, and zinc oxide.
[0027] 8. The coated steel sheet according to any one of the above 1 to 7, wherein the coating further contains a dispersant.
[0028] 9. The coated steel sheet according to claim 8, wherein the dispersant is at least one selected from the group consisting of sodium polycarboxylate, sodium polyacrylate, carboxylic acid copolymers, and sulfonic acid copolymers.
[0029] 10. The coated steel sheet according to any one of the above 1 to 9, wherein the coating further contains silica.
[0030] 11. A method for producing a coated steel sheet according to any one of the above 1 to 10, comprising applying a coating material containing an organic resin and a wax to at least one surface of a base steel sheet and drying the coating material, the organic resin is at least one selected from the group consisting of a styrene-based resin, an epoxy-based resin, a phenol-based resin, and a polyester-based resin; The method for producing a coated steel sheet, wherein the wax is a polyolefin wax having a melting point of 100° C. or higher and 145° C. or lower and an average particle size of 3.0 μm or less.
[0031] 12. The method for producing a coated steel sheet as described in claim 11, wherein the maximum temperature of the base steel sheet during the drying is 60°C or higher and the melting point of the wax or lower.
[0032] 13. The method for producing a coated steel sheet according to claim 11 or 12, wherein the proportion of the total solid content in the paint is 1% by mass or more and 30% by mass or less. Effect of the Invention
[0033] According to the present invention, the coefficient of friction between the steel sheet and the die can be significantly reduced. As a result, according to the present invention, forming can be performed without causing cracks even in areas where cracks are likely to occur during press forming. Furthermore, according to the present invention, die galling in areas with high surface pressure can be suppressed. Therefore, the coated steel sheet of the present invention has extremely good press formability and can be suitably used for forming into complex shapes. [Brief description of the drawings]
[0034] [Figure 1]1 is an example of a map image of the peak intensity ratio of a wax component to an organic resin component obtained by micro-Raman spectroscopy. [Diagram 2] 1 is an example of a map image of the peak intensity ratio of a wax component to an organic resin component obtained by micro-Raman spectroscopy. [Diagram 3] FIG. 2 is a diagram showing the distribution of wax-deficient areas obtained by analyzing the map image of FIG. 1. [Figure 4] FIG. 3 is a diagram showing the distribution of wax-deficient areas obtained by analyzing the map image of FIG. 2. [Diagram 5] FIG. 2 is a schematic front view showing a friction coefficient measuring device. [Figure 6] FIG. 6 is a schematic perspective view showing the shape and dimensions of the bead in FIG. 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0035] Hereinafter, examples of embodiments of the present invention will be described. In the following description, the unit of content "%" represents "mass %" unless otherwise specified.
[0036] (1) Coated steel sheet A coated steel sheet in one embodiment of the present invention comprises a substrate steel sheet and a coating provided on at least one surface of the substrate steel sheet.
[0037] [Coating] The coating contains an organic resin and a wax. Each component will be described below.
[0038] (Organic resin) In the present invention, the organic resin plays the role of a binder that holds the wax on the steel sheet surface. Inorganic binders have low affinity with polyolefins, so they cannot obtain the effect of providing sliding properties by forming a lubricating film. Therefore, it is important that the film contains an organic resin.
[0039] The organic resin is at least one selected from the group consisting of styrene-based resins, epoxy-based resins, phenol-based resins, and polyester-based resins. The organic resin may be a mixture of two or more resins.
[0040] As the styrene-based resin, any styrene-based resin can be used without any particular limitation. Here, the styrene-based resin is a polymer containing a styrene monomer as a constituent component, typically referring to a homopolymer of styrene and a copolymer containing styrene. The copolymer includes, for example, a copolymer of styrene and at least one selected from the group consisting of an acrylic monomer, a nitrile group, ethylene, and butadiene. The styrene-based resin is preferably a styrene-acrylic resin. By copolymerizing acrylic and styrene, press moldability is further improved compared to a case where acrylic is not contained.
[0041] The epoxy resin is not particularly limited and any epoxy resin can be used, for example, bisphenol A type epoxy resin, bisphenol F type epoxy resin, and novolac type epoxy resin.
[0042] The phenol-based resin is not particularly limited and any phenol-based resin can be used. As the phenol-based resin, it is preferable to use a resol-based phenolic resin that can be dissolved or dispersed in an aqueous solvent.
[0043] The polyester resin is not particularly limited and any polyester resin can be used. As the polyester resin, it is preferable to use a polyester resin containing a monomer having a carboxy group as a constituent component.
[0044] From the viewpoint of film removability, it is preferable that the organic resin is an alkali-soluble resin. That is, when the steel sheet is used for an automobile body or the like, painting is performed after press forming. In this case, if the organic resin is an alkali-soluble resin, the film can be removed (de-filmed) in an alkaline degreasing step performed before painting. Therefore, the subsequent painting can be performed smoothly.
[0045] The coating may contain organic resin at any ratio. However, if the ratio of organic resin is too low, the influence of components other than the organic resin becomes large, and the effect of the organic resin is relatively reduced. Therefore, from the viewpoint of enhancing the effect of the organic resin, it is preferable that the ratio of the organic resin in the coating is 30% or more. By making the ratio of the organic resin 30% or more, the effect of improving press moldability can be further enhanced, and the effects of the organic resin, such as film removal property and adhesiveness, can be fully exhibited. The ratio of the organic resin in the coating is more preferably 40% or more, and even more preferably 50% or more. On the other hand, the upper limit of the ratio of the organic resin is not particularly limited, but in order to add a certain amount of wax as described later, it is preferably 95% or less, and more preferably 90% or less.
[0046] Here, the ratio of the organic resin in the coating is defined as the ratio of the mass of the solid content of the organic resin in the coating to the total mass of all solid contents in the coating.
[0047] The mass average molecular weight of the organic resin is not particularly limited. However, if the mass average molecular weight is less than 5000, the rust prevention property may be poor. Therefore, from the viewpoint of rust prevention, the mass average molecular weight of the organic resin is preferably 5000 or more, more preferably 7000 or more, and even more preferably 9000 or more. On the other hand, if the mass average molecular weight of the organic resin exceeds 30000, the adhesiveness may be deteriorated. Therefore, from the viewpoint of adhesiveness, the mass average molecular weight of the organic resin is preferably 30000 or less, more preferably 25000 or less, and even more preferably 20000 or less.
[0048] Here, the mass average molecular weight of the organic resin is a mass average molecular weight measured based on JIS K 7252 "Plastics - Determination of average molecular weight and molecular weight distribution of polymers by size exclusion chromatography".
[0049] (wax) As the wax, a polyolefin wax is used. Polyolefin wax has low surface energy and self-lubricating properties. Therefore, by providing a coating containing polyolefin wax on the surface of the base steel sheet, excellent press formability can be obtained. In addition, the melting point of polyolefin can be relatively easily adjusted to the range described below by controlling the density and molecular weight. Among polyolefin waxes, polyethylene wax is preferably used because the greatest lubricating effect can be obtained when polyethylene wax is used.
[0050] Melting point: 100~145℃ The melting point of the polyolefin wax is 100°C or more and 145°C or less. As mentioned above, the polyolefin wax itself has self-lubricating properties. In addition, if the melting point of the polyolefin wax is within the above range, the polyolefin wax becomes semi-molten due to frictional heat caused by sliding with the die during press molding, and a lubricating film containing a mixture of organic resin and wax covers the sliding surface of the die and the steel sheet. As a result, direct contact between the die and the steel sheet is suppressed, and press moldability is significantly improved.
[0051] If the melting point of the polyolefin wax is less than 100°C, the polyolefin wax will melt completely due to the frictional heat caused by sliding during press molding, so the lubricating effect of the polyolefin wax will not be fully exerted, and the above-mentioned mold covering effect will not be obtained. Therefore, the melting point of the polyolefin wax is 100°C or higher, preferably 120°C or higher. On the other hand, if the melting point of the polyolefin wax is higher than 145°C, the polyolefin wax will not melt due to the frictional heat during press molding, so not only will the lubricating effect be insufficient, but the mold covering effect will also not be obtained. Therefore, the melting point of the polyolefin wax is 145°C or lower, preferably 140°C or lower.
[0052] Here, the melting point of the polyolefin wax is defined as the melting temperature measured based on JIS K 7121 "Method of measuring transition temperature of plastics."
[0053] Average particle size: 3.0μm or less If the average particle size of the polyolefin wax is larger than 3.0 μm, the polyolefin wax tends to aggregate in the coating, and the wax-deficient portion cannot satisfy the conditions described below. In addition, the organic resin and the wax are difficult to mix when sliding with the mold during press molding, and the above-mentioned mold covering effect is not obtained, and excellent press moldability is not obtained. Therefore, the average particle size of the polyolefin wax is 3.0 μm or less, preferably 1.5 μm or less, more preferably 0.5 μm or less, and even more preferably 0.3 μm or less. On the other hand, the lower limit of the average particle size of the polyolefin wax is not particularly limited, but if it is too small, the polyolefin wax may dissolve in the lubricating oil during press molding, and the lubrication improvement effect may decrease. In addition, since the polyolefin wax tends to aggregate in the paint, the paint stability is reduced, and coarse wax-deficient portions are easily formed. Therefore, the average particle size of the polyolefin wax is preferably 0.01 μm or more, and more preferably 0.03 μm or more.
[0054] Here, the average particle size can be measured by observing the wax particles on the surface of the coating using a scanning electron microscope (SEM). That is, the average particle size is determined by acquiring an SEM image set at a magnification corresponding to the particle size of the wax and analyzing the image. The average value of the circle-equivalent diameters of each wax particle determined by the image analysis is defined as the average particle size.
[0055] Hereinafter, a method for measuring the average particle size of wax particles using SEM will be specifically described. When measuring the average particle size of wax particles using SEM, it is necessary to sufficiently lower the acceleration voltage in order to suppress the spread and transmission of the electron beam and obtain information on the wax particles near the surface of the film. For this purpose, it is preferable to measure at an acceleration voltage of 1 kV or less. In addition, in order to prevent image damage due to charging during observation and to clearly identify the wax particles, it is preferable to carry out coating with a conductive material such as C, Au, Os, etc. The film thickness of the coating with the conductive material is preferably 2 nm or less. The measurement range of the SEM image needs to be such that the wax particles can be identified and a statistically significant number of wax particles are included. For example, when the diameter of the wax particles is 100 nm to 300 nm, it is desirable that the pixel size is 30 nm or less and the measurement range is 10 μm × 10 μm or more. Note that the SEM image may be obtained by measuring multiple fields of view continuously or arbitrarily, and multiple SEM images may be obtained so that the total satisfies the above measurement range.
[0056] The coating may contain wax in any proportion. However, if the proportion of wax in the coating is too high, the proportion of organic resin as a binder decreases relatively, and the wax component is more likely to fall off. Also, the adhesion decreases. In addition, when painting is performed, the coating may not be sufficiently removed from the steel sheet surface in the alkaline degreasing step, and sufficient degreasing may not be achieved, resulting in deterioration of paintability. Therefore, the proportion of wax in the coating is preferably 50% or less, and more preferably 30% or less.
[0057] On the other hand, there is no particular lower limit for the wax ratio. However, when the wax ratio is increased, the area ratio and average area of wax-deficient parts, which will be described later, tend to decrease, and press moldability tends to improve. Therefore, from the viewpoint of further improving press moldability, the wax ratio in the coating is preferably 5% or more, and more preferably 10% or more.
[0058] Here, the proportion of wax in the coating is defined as the proportion of the mass of the solid content of wax in the coating to the total mass of all solid contents in the coating.
[0059] (Wax deficiency area) Area ratio of wax deficiency: 20.0% or less When a coating containing an organic resin and wax is formed on the surface of a base steel sheet, the wax tends to aggregate and be distributed unevenly in the coating. As a result, regions (wax-deficient portions) in which the wax ratio is significantly low are formed in the coating. If the wax-deficient portions occupy an excessively high proportion of the surface of the coating, the desired lubricating effect is not obtained in the wax-deficient portions during press formability, resulting in a high friction coefficient. For this reason, the area ratio of the wax-deficient portions to the entire coating is set to 20.0% or less, preferably 15.0% or less, and more preferably 10.0% or less. On the other hand, the lower the area ratio, the better the press formability, so there is no particular limit, and the lower limit may be 0%.
[0060] Average area of wax deficiency: 50.0μm 2 below As described above, press formability is improved by reducing the area ratio of the wax-deficient portions. However, as a result of the investigations by the present inventors, even if the area ratio of the wax-deficient portions is 20.0% or less, if the average area of the wax-deficient portions is 50.0 μm 2 It was found that the desired press formability could not be obtained when the melting point exceeds 100° C. The reason for this is considered to be as follows.
[0061] That is, even if the total area ratio of wax-deficient parts is the same, the actual distribution of wax on the coating surface is not necessarily the same. For example, there may be a large number of relatively small wax-deficient parts dispersed on the coating surface, or there may be a small number of relatively large wax-deficient parts on the coating surface as a result of wax aggregation. When the wax-deficient parts are small in size, the adverse effect on the lubricating action is relatively minor, but when the wax-deficient parts are larger than a certain level, there is a non-negligible effect on the lubricating action. For this reason, in the present invention, the average area of wax-deficient parts is set to 50.0 μm 2 Less than or equal to 20.0 μm, preferably 2 Less than or equal to 10.0 μm, more preferably 2 On the other hand, since the smaller the average area, the better, the lower limit is not particularly limited. However, from the viewpoint of industrial production, it is preferable that the average area of the wax-deficient portion is 2.0 μm or less. 2 may be 5.0 μm or more, 2 It may be more than that.
[0062] Therefore, by controlling the wax distribution so that both the area ratio of the wax deficient parts and the average area of the wax deficient parts satisfy the above conditions, press formability can be improved extremely effectively.
[0063] Here, a wax-deficient portion is defined as a region in the coating where the ratio of the mass of wax to the mass of organic resin is 1 / 10 or less, whereas in other regions of the coating other than the wax-deficient portion, the ratio of the mass of wax to the mass of organic resin is higher than 1 / 10.
[0064] The average area and area ratio of the wax-deficient parts can be measured using microspectrophotometry, which can measure peaks attributable to the wax component and the organic resin component. Examples of the spectrophotometry include micro-Raman spectroscopy and micro-FT-IR spectroscopy. A specific method for determining the average area and area ratio of the wax-deficient parts by spectrophotometry will be described below.
[0065] First, a map image of the peak intensities corresponding to the wax component and the organic resin component is obtained by spectroscopic methods, and then a map image of the peak intensity ratio of the wax component to the organic resin component is obtained by dividing the peak intensity of the wax component obtained by the peak intensity of the organic resin component.
[0066] Next, the map image of the peak intensity ratio is converted into a map image of the mass ratio of the wax component to the organic resin component. This conversion from the intensity ratio to the mass ratio can be performed using a calibration curve. The calibration curve is created in advance by measuring a map of the peak intensity ratio using a plurality of standard samples having coatings with known mass ratios of the wax component to the organic resin component.
[0067] Thereafter, regions where the mass ratio of wax to organic resin is 1 / 10 or less are extracted as wax-deficient regions, and the area of each independent wax-deficient region is calculated using image analysis software. The area of each independent wax-deficient region is averaged to obtain the average area of wax-deficient regions. The ratio of the total area of each independent wax-deficient region to the area of the measured field of view is calculated to obtain the area ratio of wax-deficient regions.
[0068] The peaks to be measured when determining the area ratio and average area of the wax-deficient parts may be those attributable to the wax component and the organic resin component, respectively. However, in order to reduce noise, it is preferable to use a peak with as high intensity as possible. For example, in micro-Raman spectroscopy, the peak attributable to the polyolefin wax is 1295 cm, which corresponds to the twist of CH2. -1 It is preferable to use the peak at 1000 cm corresponding to the stretching vibration of the aromatic ring chain as a peak attributable to the organic resin components, such as styrene resin, epoxy resin, phenol resin, and polyester resin. -1 It is preferable to use the peak of
[0069] In addition, the measurement range of the map image of the peak intensity ratio is preferably 80 μm × 80 μm or more because it is necessary to include a statistically significant number of wax deficiency areas. The measurement range may be one continuous visual field or a combination of multiple visual fields.
[0070] As described above, the upper limit of the average particle size of the wax in the present invention is 3.0 μm. Therefore, from the viewpoint of determining the aggregation state of the wax, the interval between each measurement point of the map image is preferably 3 μm or less, and more preferably 2 μm or less.
[0071] Figures 1 and 2 are example map images of the peak intensity ratio of the wax component to the organic resin component obtained by micro-Raman spectroscopy. The measurement range was 100 μm × 100 μm, and the measurement conditions were as described above. Figure 1 is a map image of the peak intensity ratio of a film in which wax is distributed relatively uniformly, while Figure 2 is a map image of the peak intensity ratio of a film in which wax is distributed non-uniformly (a film in which wax is aggregated).
[0072] Figures 3 and 4 show the distribution of wax deficient areas obtained by analyzing the map images of peak intensity ratios shown in Figures 1 and 2, respectively. In the above analysis, first, the map images of peak intensity ratios shown in Figures 1 and 2 were converted into map images of mass ratios using a calibration curve created in advance. Then, using image analysis software, the wax deficient areas in the map images of mass ratios were displayed as white areas. The area ratio and average area of the wax deficient areas were 0.3% and 6.3 μm in Figure 3, respectively. 2 , 33.6% in Fig. 4, 112.1 μm 2 It was.
[0073] [Rust inhibitor] Even if the coating does not contain a rust inhibitor, rust will not occur in a normal storage environment. However, from the viewpoint of further improving rust prevention, it is preferable that the coating further contains a rust inhibitor.
[0074] The rust inhibitor is not particularly limited and any rust inhibitor can be used, but it is preferable to use at least one selected from the group consisting of aluminum salts of phosphoric acids, zinc salts, and zinc oxide. Here, phosphoric acids include orthophosphoric acid as well as condensed phosphoric acids such as pyrophosphoric acid, tripolyphosphoric acid, tetrapolyphosphoric acid, and metaphosphoric acid. By using these rust inhibitors, it is possible to achieve a more excellent rust prevention effect and further reduce deterioration of paint stability.
[0075] The content of the rust inhibitor is not particularly limited, but if the content of the rust inhibitor is too low, sufficient effect may not be obtained. In particular, when the coated steel sheet is stored in a coiled stacked state, rust is likely to occur due to moisture absorption. From the viewpoint of preventing rust from occurring even under such a harsh environment, it is preferable that the proportion of the rust inhibitor in the film is 5% or more. On the other hand, if the proportion of the rust inhibitor in the film exceeds 30%, the adhesion may deteriorate. In addition, the rust inhibitor may precipitate in the paint state, and the paint stability may deteriorate. Therefore, it is preferable that the proportion of the rust inhibitor in the film is 30% or less.
[0076] Here, the ratio of the rust inhibitor in the coating is defined as the ratio of the mass of the rust inhibitor in the coating to the total mass of all solids in the coating.
[0077] [Dispersant] From the viewpoint of improving the dispersibility of the coating components, it is preferable that the coating further contains a dispersant. As the dispersant, any dispersant can be used without any particular limitation, but it is preferable to use an anionic polymer dispersant. An anionic polymer dispersant is particularly effective in improving the dispersibility of particles of several μm or less, and can be adsorbed to polyolefin wax. As the anionic polymer dispersant, it is preferable to use at least one selected from the group consisting of sodium polycarboxylate, sodium polyacrylate, carboxylic acid copolymer, and sulfonic acid copolymer.
[0078] The proportion of the dispersant in the film is not particularly limited, but is preferably 0.5% or more. When the proportion of the dispersant in the film is 0.5% or more, the dispersibility of the wax in the paint is improved, and the uniformity of the wax distribution in the obtained film is improved. As a result, it becomes easier to achieve the desired wax distribution, and the press moldability is further improved. On the other hand, when the proportion of the dispersant in the film exceeds 5%, the adhesion may deteriorate. Therefore, the proportion of the dispersant in the film is preferably 5% or less.
[0079] Here, the ratio of the dispersant in the coating refers to the ratio of the mass of the dispersant in the coating to the total mass of the solid contents of all the components in the coating.
[0080] (silica) From the viewpoint of improving the water repellency and rust prevention of the coating, it is preferable that the coating further contains silica. Furthermore, the inclusion of silica suppresses the precipitation of the rust inhibitor contained in the paint, thereby improving the paint stability.
[0081] The silica is not particularly limited and any silica can be used. The silica is preferably colloidal silica. The average particle size of the colloidal silica is not particularly limited, but is preferably 5 nm or more. The average particle size of the colloidal silica is preferably 200 nm or less. The average particle size of the colloidal silica can be measured by dynamic light scattering. Specifically, first, the particle size distribution based on scattering intensity is measured by dynamic light scattering. Then, the particle size distribution is converted from the scattering intensity standard to the volume standard. The median diameter D50 in the obtained volume-based particle size distribution is defined as the average particle size of the colloidal silica.
[0082] The proportion of silica in the film is preferably 1% or more. By making the proportion of silica in the film 1% or more, the water repellency of the film is increased, and the rust prevention property is further improved. On the other hand, if the proportion of silica in the film exceeds 10%, the adhesion may deteriorate. Therefore, the proportion of silica in the film is preferably 10% or less.
[0083] Here, the proportion of silica in the coating refers to the proportion of the mass of silica in the coating to the total mass of the solid contents of all components in the coating.
[0084] The ratio of each component contained in the coating can be calculated from the solid mass of each coating component when the paint is formulated.
[0085] The coating may contain any other components in addition to the organic resin, wax, rust inhibitor, dispersant, and silica, such as surface conditioners and defoamers that are generally added to paints.
[0086] Adhesion amount: 0.3g / m 2 End The coating weight is 0.3g / m 2 If the amount is less than 0.3 g / m, the wax is likely to aggregate during the period from when the coating is applied to when it is dried, and the desired wax distribution cannot be obtained, resulting in poor press moldability. 2 As described later, the final wax distribution is affected by the surface roughness of the substrate steel sheet. Therefore, from the viewpoint of easily obtaining the desired wax distribution even when the substrate steel sheet has a large surface roughness, the coating weight per side is set to 0.4 g / m 2 It is preferable that the density is 0.6 g / m or more. 2 More preferably, it is 0.8 g / m or more. 2 On the other hand, the upper limit of the coating weight is not particularly limited, but is preferably 2.5 g / m 2 If the coating exceeds this limit, the weldability, removal property, and adhesion may deteriorate. Therefore, the coating weight per side should be 2.5 g / m 2 It is preferable that:
[0087] The coating weight can be determined by removing the coating from the coated steel sheet and dividing the difference in mass before and after coating removal by the area of the steel sheet. The coating can be removed by any method that can remove only the coating without damaging the underlying steel sheet. Typically, a solvent capable of dissolving the organic resin that constitutes the coating (such as an organic solvent) or a stripping agent containing such a solvent may be used. When the coating is an alkali-soluble type, it is preferable to use an alkaline degreaser, as described in the examples.
[0088] [Substrate steel plate] As described above, in the present invention, excellent press formability is achieved by controlling the components of the coating and the distribution of wax in the coating. Therefore, the base steel sheet is not particularly limited and any steel sheet can be used. The base steel sheet may be either a cold-rolled steel sheet or a hot-rolled steel sheet.
[0089] The tensile strength TS of the base steel sheet is not particularly limited, but if it is too low, the strength of the finally obtained press-formed member may be insufficient. Therefore, the tensile strength of the base steel sheet is preferably 260 MPa or more. On the other hand, the upper limit of the tensile strength is also not particularly limited. For example, when a high-strength steel sheet having a tensile strength of 440 MPa or more is used as the base steel sheet, the surface pressure during press forming becomes high. However, according to the present invention, since the friction coefficient between the steel sheet and the die can be significantly reduced, even under such high surface pressure conditions, the occurrence of cracks and die galling is suppressed, and good press formability is obtained. Therefore, the tensile strength of the base steel sheet may be 440 MPa or more. However, if the tensile strength is excessively high, it becomes difficult to press-form into a complex shape. Therefore, from the viewpoint of press formability into a complex shape, the tensile strength of the base steel sheet is preferably 440 MPa or less.
[0090] The thickness of the base steel sheet is not particularly limited, but if it is too thin, the strength of the final press-formed part may be insufficient. Therefore, the thickness of the base steel sheet is preferably 0.5 mm or more. On the other hand, the upper limit of the thickness is not particularly limited, but if it is too thick, it becomes difficult to press-form into a complex shape. Therefore, the thickness of the base steel sheet is preferably 4.0 mm or less.
[0091] The surface roughness of the above-mentioned base steel sheet (surface roughness of the base steel sheet before the coating is formed) is not particularly limited. However, when the arithmetic mean roughness Ra of the base steel sheet surface is larger than 2.5 μm, the unevenness of the base steel sheet surface is large, so that the coating formed in the recessed parts is less likely to come into contact with the die during press forming. In addition, the amount of coating attached to the protruding parts is smaller than that of the recessed parts, so that it is difficult to obtain a desired wax distribution, and as a result, the effect of improving press formability may be reduced. Therefore, from the viewpoint of further improving press formability, it is preferable to set Ra to 2.5 μm or less. On the other hand, when Ra is smaller than 0.4 μm, fine scratches that may occur during press forming are easily noticeable. In addition, when Ra is smaller than 0.4 μm, galling may occur during press forming. Therefore, it is preferable to set Ra to 0.4 μm or more.
[0092] Here, the arithmetic mean roughness Ra of the base steel sheet can be measured in accordance with JIS B 0633:2001 (ISO 4288:1996). For example, when Ra is greater than 0.1 and equal to or less than 2, Ra is obtained from a roughness curve measured with a cutoff value, a reference length of 0.8 mm, and an evaluation length of 4 mm. When Ra is greater than 2 and equal to or less than 10, Ra is obtained from a roughness curve measured with a cutoff value, a reference length of 2.5 mm, and an evaluation length of 12.5 mm.
[0093] (2) Manufacturing method Next, a method for producing a coated steel sheet of the present invention will be described. In one embodiment of the present invention, a coating material containing an organic resin and a wax is applied to at least one surface of a base steel sheet, and then dried to produce the coated steel sheet. Note that, unless otherwise specified, the same applies as in the description of the coated steel sheet.
[0094] The coating material may be, for example, an organic resin solution in which an organic resin is dissolved in a solvent, or an organic resin emulsion in which an organic resin is dispersed in a solvent, to which a wax has been added. As the solvent, one or both of water and an organic solvent may be used, but it is preferable to use water.
[0095] The ratio of the total solid content in the paint is not particularly limited, but is preferably 1 to 30%. If the ratio of the total solid content in the paint is less than 1% or more than 30%, uneven coating may occur and the desired wax distribution may not be obtained. Here, the ratio of the total solid content in the paint refers to the concentration of the total solid content in the paint, that is, the ratio of the mass of the solid content to the total mass of the paint (including the solvent).
[0096] The coating of the paint on the base steel sheet can be carried out by any method without any particular limitation. Examples of the coating method include a method using a roll coater or a bar coater, a spray method, a dipping method, and a brush coating method. In the coating method, the coating weight of the finally obtained coated steel sheet per one side of the steel sheet is 0.3 g / m2 in terms of dry mass. 2 Apply paint so that the above is achieved.
[0097] The method for drying the coating material after application is not particularly limited and may be any method, such as drying with hot air, drying with an IH heater, or drying with infrared radiation.
[0098] The maximum temperature of the steel sheet during drying is preferably 60° C. or higher and the melting point of the wax used or lower. If the maximum temperature is lower than 60° C., it takes a long time to dry and the rust prevention properties may be poor. On the other hand, if the maximum temperature exceeds the melting point of the wax, the wax melts and coalesces, causing the particle size to become coarse, making it difficult to obtain the desired wax distribution. EXAMPLES
[0099] The present invention will be described below with reference to examples, but the present invention is not limited to the following examples.
[0100] A coating was formed on the surface of a base steel sheet in the following manner to produce a coated steel sheet.
[0101] First, four types of substrate steel sheets were prepared, each having the arithmetic mean roughness Ra shown in Table 1. Substrate steel sheets A to C are cold-rolled steel sheets with a thickness of 0.8 mm, and substrate steel sheet D is a hot-rolled steel sheet with a thickness of 2.0 mm. The substrate steel sheets A to D are all SPCD (JIS G 3141) and SPHD (JIS G 3131) with tensile strength of 270 MPa class.
[0102] In addition, paints were prepared with the compositions shown in Tables 2 and 3. The ratio of each component in Tables 2 and 3 is the ratio of the solid mass of each component to the total mass of all solids contained in the paint. Colloidal silica with a volume average particle size of 9 nm was used as the silica. The molecular weight of the organic resin and the melting point and average particle size of the wax shown in Tables 2 and 3 were measured by the methods described above.
[0103] The paint was applied to the surface of the base steel sheet using a bar coater, and the steel sheet surface was heated and dried using an IH heater so that the maximum temperature reached was 80° C., to obtain a coated steel sheet. The combinations of base steel sheet and paint used were as shown in Tables 4 to 7. For comparison, in some comparative examples, no coating was formed, and the base steel sheet was directly subjected to the evaluation described below.
[0104] (film adhesion amount) The coating weight of the obtained coated steel sheet was measured. Specifically, the coating was removed from the coated steel sheet, and the difference in mass before and after the coating removal was divided by the area of the steel sheet to determine the coating weight. The coating was removed by immersing the coated steel sheet in a degreasing solution with a degreasing agent concentration of 20 g / L and a temperature of 40° C. for 300 seconds. As the degreasing agent, an alkaline degreasing agent, Fine Cleaner E6403 (manufactured by Nippon Parkerizing Co., Ltd.), was used. It was confirmed separately by the same method as in the coating removal test described below that the coating was completely removed under the above conditions. The coating coating weights shown in Tables 4 to 7 are values per one side of the steel sheet.
[0105] (Wax deficiency area) Next, the area ratio and average area of wax-deficient parts on the coating surface of the obtained coated steel sheets were evaluated by the following procedure.
[0106] First, five test pieces of 10 mm x 10 mm size were cut out from each of the coated steel plates. The vicinity of the center of the test pieces was measured using a micro-Raman device (LabRAM HR Evolution manufactured by Horiba) to obtain map images of the peak intensities corresponding to the wax component and the organic resin component. The measurement range was 100 μm x 100 μm, and the measurement interval was 1 μm. The peak of the wax component was 1295 cm -1 The peak of the organic resin component is 1000 cm -1 The peaks from each were used.
[0107] Next, a map image of the peak intensity ratio of the wax component to the organic resin component was created by dividing the peak intensity of the wax component in the obtained map image by the peak intensity of the organic resin component. The map image of the peak intensity ratio was then converted into a map image of the mass ratio of the wax component to the organic resin component using a calibration curve created in advance.
[0108] In the map image of the mass ratio obtained, the measurement points where the mass ratio of wax to organic resin was 1 / 10 or less were determined to be wax deficient areas, and the area ratio and average area of the wax deficient areas were calculated. 2The following wax deficient areas were not treated as wax deficient areas and were excluded from the calculation of the area ratio and average area.
[0109] The above measurements were performed on five test pieces, and the obtained area ratios and average areas, as well as the average values thereof, were adopted as the area ratios and average areas of the wax deficient parts. The obtained results are shown in Tables 4 to 7.
[0110] Next, the properties of the resulting coated steel sheets were evaluated by the following procedures.
[0111] (Press formability) The press formability is correlated with the sliding property, i.e., the friction coefficient of the steel sheet surface, and the lower the friction coefficient, the better the press formability. Therefore, in order to evaluate the press formability, the friction coefficient of the obtained coated steel sheet was measured by the following procedure.
[0112] FIG. 5 is a schematic front view showing a friction coefficient measuring device. As shown in the figure, a friction coefficient measuring sample 1 taken from a coated steel plate is fixed to a sample stage 2, and the sample stage 2 is fixed to the upper surface of a horizontally movable slide table 3. A vertically movable slide table support 5 having a roller 4 in contact with the slide table 3 is provided on the lower surface of the slide table 3, and a first load cell 7 is attached to the slide table support 5 to measure the pressing load N applied by the bead 6 to the friction coefficient measuring sample 1 by pushing up the slide table 3. A second load cell 8 is attached to one end of the slide table 3 to measure the sliding resistance force F for moving the slide table 3 horizontally while the pressing force is applied. The test was performed by applying press cleaning oil Pleton R352L manufactured by Sugimura Chemical Industry Co., Ltd. as a lubricant to the surface of the sample 1.
[0113] Figure 6 is a schematic perspective view showing the shape and dimensions of the bead used. The bead 6 slides while its underside is pressed against the surface of the sample 1. The shape of the bead 6 shown in Figure 6 is 10 mm wide, 59 mm long in the sliding direction of the sample, and the lower parts of both ends in the sliding direction are curved surfaces with a curvature of 4.5 mmR, and the underside of the bead against which the sample is pressed has a flat surface with a width of 10 mm and a length of 50 mm in the sliding direction.
[0114] The friction coefficient measurement test was performed using the bead shown in Figure 6, with a pressing load N of 400 kgf and a sample pull-out speed (horizontal movement speed of the slide table 3) of 20 cm / min. The friction coefficient μ between the sample and the bead was calculated by the formula: μ = F / N.
[0115] The obtained values of the friction coefficient are shown in Tables 4 to 7. When the friction coefficient was 0.115 or less, the press moldability (slidability) was determined to be good.
[0116] (Weldability) When press-formed parts obtained by press-forming coated steel sheets are used for automobile bodies, welding is generally performed in the assembly process. For this reason, it is desirable that coated steel sheets have excellent weldability in addition to press formability. Therefore, the weldability of coated steel sheets was evaluated. Specifically, a continuous welding test was performed on the coated steel sheets under the following conditions: electrode used: DR type Cr-Cu electrode, pressure: 150 kgf, current application time: 10 cycles / 60 Hz, welding current: 7.5 kA, and the number of continuous welding points was calculated. If the number of continuous welding points was 5,000 points or more, the weldability was evaluated as "good", and if the number was less than 5,000 points, the weldability was evaluated as "inadequate".
[0117] (removable) Assuming that the coated steel sheet according to the present invention is used for automotive applications, the removability during degreasing was evaluated. To determine the removability of the coating, first, each coated steel sheet was immersed in a degreasing solution with a degreasing agent concentration of 20 g / L and a temperature of 40° C. for a predetermined period of time, and then degreased by washing with tap water. As the degreasing agent, an alkaline degreasing agent Fine Cleaner E6403 (manufactured by Nippon Parkerizing Co., Ltd.) was used.
[0118] Next, the surface carbon intensity of the test piece after degreasing was measured using an X-ray fluorescence analyzer. The coating peeling rate was calculated according to the following formula using the measured surface carbon intensity, the previously measured surface carbon intensity before degreasing, and the surface carbon intensity of the base steel sheet. Film peeling rate (%) = [(surface carbon strength before degreasing - surface carbon strength after degreasing) / (surface carbon strength before degreasing - surface carbon strength of base steel plate)] x 100 Here, the surface carbon strength of the substrate steel sheet refers to the surface carbon strength of the substrate steel sheet before the coating is formed.
[0119] The above test was carried out by varying the immersion time in the degreasing solution, and the immersion time in the alkaline degreasing solution at which the coating peeling rate was 98% or more was determined. The immersion times thus determined are shown as "coating removal times" in Tables 4 to 7. When the coating removal time was 120 seconds or less, it was determined that the coating had good removability.
[0120] (Rust prevention) Assuming that the coated steel sheet is stored in a coiled state, the rust prevention properties of the overlapping state were evaluated. Specifically, a test piece measuring 150 mm x 70 mm was taken from the coated steel sheet, and the surface of the test piece was coated with rust prevention oil at a rate of 1.0 g / m per side. 2 The two test pieces were then placed one on top of the other and the surface pressure was 0.02 kgf / mm 2 The specimen was kept in an environment with a temperature of 50°C and a humidity of 95% with a load applied.
[0121] The inside surfaces of the overlapping pieces were checked every seven days, and the number of days until rust appeared was evaluated. A rating of "excellent" was given if it took 56 days or more for rust to appear, "good" if it took 21 days or more, and "fair" if it took less than 21 days.
[0122] (Adhesiveness) When press-formed parts obtained by press-forming coated steel sheets are used for automobile bodies, etc., adhesion may be performed during the assembly process. Therefore, it is desirable for coated steel sheets to have excellent adhesion in addition to press formability. Therefore, the adhesion of coated steel sheets was evaluated. Specifically, two test pieces of 100 x 25.4 mm in size were taken from each coated steel sheet and immersed in rust-preventive oil. After removing the test pieces from the rust-preventive oil, they were stood upright for 24 hours to remove excess oil.
[0123] Next, an epoxy adhesive was applied uniformly to a thickness of 0.2 mm over an area of 25.4 mm x 13 mm on the surface of the test piece. The two test pieces were then overlapped and clamped with clips, and baked at 180°C for 20 minutes to dry and harden. After cooling, a shear tensile test was performed using an autograph tester to measure the shear adhesive strength. A shear adhesive strength of 20 MPa or more was deemed to be good adhesiveness.
[0124] As can be seen from the results shown in Tables 4 to 7, all of the coated steel sheets satisfying the conditions of the present invention had a friction coefficient of 0.115 or less and had excellent press formability. In contrast, all of the coated steel sheets not satisfying the conditions of the present invention had a friction coefficient higher than 0.115 and had poor press formability.
[0125] INDUSTRIAL APPLICABILITY As described above, the coated steel sheet of the present invention has excellent sliding properties (press formability) during press forming, and can be suitably used in a variety of applications including automobile body applications.
[0126] [Table 1]
[0127] [Table 2]
[0128] [Table 3]
[0129] [Table 4]
[0130] [Table 5]
[0131] [Table 6]
[0132] [Table 7] [Explanation of symbols]
[0133] 1. Sample for measuring friction coefficient 2 Sample stage 3 Slide table 4. Lola 5 Slide table support 6 Beads 7 First load cell 8 Second Load Cell 9. Rail
Claims
1. A coated steel sheet comprising a base steel sheet and a coating containing an organic resin and a wax provided on at least one surface of the base steel sheet, The arithmetic average roughness Ra of the base steel sheet surface is 0.4 μm or more and 2.5 μm or less, the organic resin is at least one selected from the group consisting of a styrene-based resin, an epoxy-based resin, a phenol-based resin, and a polyester-based resin; The wax is a polyolefin wax having a melting point of 100° C. or higher and 145° C. or lower and an average particle size of 3.0 μm or less, the coating has a wax-deficient portion, which is defined as a region in which the ratio of the mass of the wax to the mass of the organic resin is 1 / 10 or less, and the area ratio of the wax-deficient portion to the entire coating is 20.0% or less; The average area of the wax deficient portion is 50.0 μm 2 is as follows: The coating weight per side is 0.3 g / m 2 That's it, coated steel sheet.
2. The proportion of the organic resin in the coating is 30% by mass or more and 95% by mass or less, The coated steel sheet according to claim 1 , wherein the wax content in the coating is 5 mass % or more and 50 mass % or less.
3. The coating weight per side is 2.5 g / m 2 The coated steel sheet according to claim 1 or 2, wherein:
4. The coated steel sheet according to claim 1 or 2, wherein the organic resin is an alkali-soluble resin.
5. The coated steel sheet according to claim 1 or 2, wherein the coating further contains a rust inhibitor.
6. The coated steel sheet according to claim 5, wherein the rust inhibitor is at least one selected from the group consisting of aluminum salts of phosphoric acids, zinc salts, and zinc oxide.
7. The coated steel sheet according to claim 1 or 2, wherein the coating further contains a dispersant.
8. 8. The coated steel sheet according to claim 7, wherein the dispersant is at least one selected from the group consisting of sodium polycarboxylate, sodium polyacrylate, carboxylic acid copolymers, and sulfonic acid copolymers.
9. The coated steel sheet according to claim 1 or 2, wherein the coating further contains silica.
10. 2. The method for producing a coated steel sheet according to claim 1, wherein a paint containing an organic resin and a wax is applied to at least one surface of a base steel sheet and dried, the organic resin is at least one selected from the group consisting of a styrene-based resin, an epoxy-based resin, a phenol-based resin, and a polyester-based resin; The method for producing a coated steel sheet, wherein the wax is a polyolefin wax having a melting point of 100° C. or higher and 145° C. or lower and an average particle size of 3.0 μm or less.
11. The method for producing a coated steel sheet according to claim 10, wherein a maximum temperature of the base steel sheet during the drying is 60°C or higher and is lower than a melting point of the wax.
12. The method for producing a coated steel sheet according to claim 10 or 11, wherein a proportion of a total solid content in the paint is from 1 mass % to 30 mass %.
Citation Information
Patent Citations
Colored lubrication-treated galvanized steel sheet having high edge face corrosion resistance and its production
JP1996013156A
Pigmented lubricant-treated steel plate and manufacture thereof
JP1996187819A
Galvanized steel sheet covered with alkali-soluble resin coating film having excellent adhesiveness by adhesive
JP1997170059A
Resin covered metal plate excellent in press molding property and corrosion resistance and manufacture thereof
JP1998029266A
Resin coated metal plate with mold drag resistance and corrosion resistance and its manufacture
JP1998052881A